Radiotherapy of patients with pacemakers and cardioverter-defibrillators - Mavungo, Ariela Bertini Cumba (Univerzita Pardubice, 2022)
This bachelor's thesis examines how radiotherapy may affect the functioning of cardiovascular implantable electronic devices, specifically pacemakers and cardioverter-defibrillators, aiming to provide accurate information on how often error occurs and possible reccomendations to facilitate the management of patients and increase care effectiveness. The first part focuses on the heart's electrical conduction system and the rhythm pathology, cardiovascular implantable electronic devices, the construction of pacemakers and implantable cardioverter-defibrillators, its functioning, patient management, and radiation therapy treatments and its modalities. The second part will provide an overview of the incidence of device malfunction, focusing on the consequences of radiation in patients with cardiac devices malfunctions.
Radioterapie pacientů s kardiostimulátorem a kardioverter-defibrilátorem
Keywords: arytmie; implantovaný srdeční elektronický přístroji; cor; porucha přístroje; kardioverter-defibrilátor; kardiostimulátor; radioterapie; arrhythmia; cardiovascular implantable electronic devices; cor; device malfunction; implantable cardioverter-defibrillator; pacemaker; radiotherapy.